LEGAL CERTAINTY OF CREDITORS’ RIGHTS IN THE BANKRUPTCY OF CONDOMINIUM UNITS (APARTMENTS): A Case Study of Decision No. 40/Pdt.Sus.PKPU/2023/PN Niaga.Sby and Decision No. 63/Pdt.Sus-Gugatan Lain-Lain/2023/PN Niaga.Sby - Arlisah Sri Utami (jfpublisher, 2025)
Global economic development has an influence on legal development, especially economic law. Bankruptcy can occur due to the rapid development of the economy and trade where various kinds of debt and receivables problems arise in society. The purpose of this study is to find out and understand the legal considerations of judges in decision number: 40/Pdt.Sus-PKPU/2023/PN. Niaga.Sby and number: 63/Pdt.Sus-LawsuitLainLain/2023/PN. Niaga.Sby. and to know and understand the legal certainty of creditors' rights to bankruptcy after the decision. This research method uses normative legal research. Approaches in normative (dogmatic) legal research include the statute approach or legislation-regulation approach, conceptual approach, historical approach and comparative approach. Legal protection of creditors from the object of the right of dependency from the attempt to confiscate the guarantee by a third party to hand over a guarantee for an agreement that has been agreed upon by the debtor which is the obligation of the bankrupt debtor from the bankruptcy property. If the creditor has paid in full for an object or service in dispute, the creditor receives legal protection to be removed from the bankruptcy estate according to the Supreme Court Circular Letter No. 4 of 2016.